THE EFFECT OF MOTIVATION AND SOLAR DRYER DOME ASSISTANCE ON THE PERFORMANCE OF THE TRUBUS FARMER GROUP IN WEST PRINGSEWU VILLAGE, PRINGSEWU SUB-DISTRICT, PRINGSEWU REGENCY - Yety, Yety; Dunan, Hendri; Barusman, Andala Rama Putra (Program Studi Magister Manajemen, 2024)
This study aims to determine the effect of motivation and solar dryer dome assistance on the performance of the Trubus Farmer Group in West Pringsewu Village, Pringsewu Sub-district, Pringsewu Regency. The population in the study were members of the Trubus farmer group in West Pringsewu Village, Pringsewu Sub-district, Pringsewu Regency. In this study, the entire population of 25 farmer group members was sampled. The quantitative data analysis model used is multiple linear regression analysis. The results showed that motivation (X1) had a positive effect on the performance (Y) of Trubus farmer group members in West Pringsewu Village, Pringsewu Sub-district, Pringsewu Regency, Solar Dryer Dome Assistance (X2) had a positive effect on the performance (Y) of Trubus farmer group members in West Pringsewu Village, Pringsewu Sub-district, Pringsewu Regency. Motivation (X1) and Solar Dryer Dome Assistance (X2) simultaneously affect the performance (Y) of the Trubus farmer group in West Pringsewu Village, Pringsewu Sub-district, Pringsewu Regency.